The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1007/pl00007513
|View full text |Cite
|
Sign up to set email alerts
|

How much does it cost to preserve a larynx?

Abstract: Various studies report an increase in costs when induction chemotherapy is included in the treatment of advanced laryngeal cancer, but to our knowledge no studies have yet compared the economic costs of total laryngectomy versus induction chemotherapy in the treatment of advanced laryngeal cancer. We have conducted a retrospective study comparing the costs of treatment and survival in 96 patients with a T3N0-1 glottic carcinoma. Findings showed that the average cost per patient in the group of patients treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 14 publications
1
5
0
1
Order By: Relevance
“…According to the decision-analysis model in this study, total laryngectomy with postoperative radiotherapy yields lower direct medical costs by $2914 per patient com-(REPRINTED) ARCH OTOLARYNGOL HEAD NECK SURG/ VOL 131, JAN 2005 pared with an organ preservation protocol in the management of advanced laryngeal cancer. This finding agrees with that reported by Leon and colleagues, 33 who retrospectively reviewed medical records from 96 patients from Spain with stage III glottic tumors and found surgery to be less expensive than organ preservation by €600.…”
Section: Commentsupporting
confidence: 92%
“…According to the decision-analysis model in this study, total laryngectomy with postoperative radiotherapy yields lower direct medical costs by $2914 per patient com-(REPRINTED) ARCH OTOLARYNGOL HEAD NECK SURG/ VOL 131, JAN 2005 pared with an organ preservation protocol in the management of advanced laryngeal cancer. This finding agrees with that reported by Leon and colleagues, 33 who retrospectively reviewed medical records from 96 patients from Spain with stage III glottic tumors and found surgery to be less expensive than organ preservation by €600.…”
Section: Commentsupporting
confidence: 92%
“…Although some trials have shown an improvement in some components of quality of life (8, 30) many others have described equivalent results (31)(32)(33)(34). Furthermore, cost consideration may be an important factor in decision making for the treatment of advanced laryngeal cancer (35,36).…”
Section: Discussionmentioning
confidence: 95%
“…Leon et al [34] compared the costs of total laryngectomy to induction chemotherapy.The average cost per laryngectomized patient with or without radiotherapy was €5,853 (2001 €6,002) while the average cost for those patients treated with induction chemotherapy was €6,452 (€6,616). Among patients who received induction chemotherapy 46% (16 of 35) did not have a laryngectomy.…”
Section: Cost-comparison Analyses Across Treatmentsmentioning
confidence: 99%